ANALISIS TANGGUNG JAWAB PIDANA PADA PELAKU TINDAK PIDANA PERCOBAAN ABORSI YANG MELIBATKAN JASA OKNUM DOKTER (STUDI PUTUSAN NO. 1106/PID.SUS/2018/PN.PLG) - Miko Sapta Sera K; Nashriana Nashriana; KN Sofyan Hasan (Lex LATA, 2022)
Abortion is a problem that has violated ethics, laws and religions of various parties. Based on this, the problems of the thesis included the following aspects: (1) the judges considerations of imposing criminal sanctions on individual doctors, (2) criminal responsibility, (3) the perspective of medical ethics in conducting attempted abortion in the Decision No. 1106/Pid Sus/2018/PN.Plg. and (4) regulating abortion in the future The research method used was juridical normative (legal research). The results of the research showed that in imposing criminal sanctions, the judges considered juridical decisions more than non-juridical ones, criminal responsibility in which individual doctors conducted attempted abortion in the Decision No 1106/Pid Sus/2018/PN Plg had the elements of dualist view which fulfilled subjective and objective clements, regarding the ethical perspective of medical profession towards the crime of committing attempted abortion in the Decision No. 1106 Pid Sus 2018 PN Plg, the individual doctors had violated the code of ethics and doctor's oath, regarding eriminal-abortion laws in the future, it is necessary to reform criminal law with the policy-oriented approach as well as the value-onented approach. Keywords:Criminal Responsibility, Attempted Abortion, Medical Profession Code Of Ethics